Reservoir Characterization of the Upper Part of Qamchuqa Formation from Miran and Bazian Oilfields in Kurdistan Region, NE Iraq - Danyar A. Salih; Fouad Qader (Tikrit Journal of Pure Science, 2023)
Reservoir characterization of the upper part of Qamchuqa Formation at the wells of Miran West-2 (MW-2) and Bazian-1 (BN-1) is studied. This formation typically has low shale content at the BN-1 well. At the same time, in the MW-2 well, the middle part of the studied formation is dominated by shaly and shale intervals, possibly affected by the Sarmord and Balambo depositional environments. Although the upper part of Qamchuqa Formation is mainly composed of dolomite with minor dolomitic limestone, marl and shale are occasionally present. Furthermore, porosity values are commonly less than 15% in both wells; nevertheless, there are a few intervals where porosity significantly increases. The formation at the BN-1 well has a higher porosity than the MW-2 well. Moreover, the secondary porosity is relatively low as 4.0% at the MW-2 well, while in the well of BN-1, it ranges between < 4.0% and 7.5%. The measured permeability of the formation suggests good permeability. According to the shale volume, porosity, and permeability, the upper part of Qamchuqa Formation is subdivided into three reservoir units. RU 1 at the MW-2 well and RU 2 at the BN-1 well have the most substantial reservoir properties. However, the lowest reservoir quality appears within RU 1 of the BN-1 well and RU 2 at the well of MW-2. Additionally, residual hydrocarbons constitute an extensive fraction of the pore spaces, while tiny portions of the moveable one can be discovered along all reservoir units of the formation. Finally, considering the hydrocarbon movability of the MW-2 well, the upper part of Qamchuqa Formation is defined by primarily movable oils in RU 1 and 2. In contrast, moveable oils are detected in almost all of the reservoir units of the BN-1 well.